2020
DOI: 10.1371/journal.pone.0244455
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association analysis of Russian wheat aphid (Diuraphis noxia) resistance in Dn4 derived wheat lines evaluated in South Africa

Abstract: Russian wheat aphid (RWA; Diuraphis noxia Kurdjumov) resistance on the 1D chromosome of wheat has been the subject of intensive research. Conversely, the deployment of the Dn4 derived RWA resistant varieties diminished in recent years due to the overcoming of the resistance it imparts in the United States of America. However, this resistance has not been deployed in South Africa despite reports that Dn4 containing genotypes exhibited varying levels of resistance against the South African RWA biotypes. It is po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…Comparing these findings with the study by Li and Peng [ 59 ], two distinct groups were identified in the wheat germplasm using the STRUCTURE Bayesian analysis, with the highest ΔK value obtained at 2 suggesting the wheat germplasm could be divided into two groups. Following a population structure study, Kisten et al [ 35 ] separated the wheat panel into two unique clusters. Cluster 2 featured 67 bulked samples of spring-type breeding lines created in Montana, United States, whereas Cluster 1 contained 102 bulked samples of winter-type cultivars and breeding lines from the United States and Turkey.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparing these findings with the study by Li and Peng [ 59 ], two distinct groups were identified in the wheat germplasm using the STRUCTURE Bayesian analysis, with the highest ΔK value obtained at 2 suggesting the wheat germplasm could be divided into two groups. Following a population structure study, Kisten et al [ 35 ] separated the wheat panel into two unique clusters. Cluster 2 featured 67 bulked samples of spring-type breeding lines created in Montana, United States, whereas Cluster 1 contained 102 bulked samples of winter-type cultivars and breeding lines from the United States and Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Xgwm111 , which is linked to other resistance-related genes, has been reported to be associated with aphid resistance [ 63 , 64 ]. Previous association mapping studies by Peng et al [ 58 ], Dahleen et al [ 65 ], Li and Peng [ 59 ], and Kisten et al [ 35 ] have also identified significant associations between SSR loci or SNP markers and aphid resistance or related traits in wheat germplasm. The results obtained from association mapping provide valuable insights into the genetic basis of aphid resistance mechanism in wheat, contributing towards understanding of the underlying loci and potential markers associated with resistance traits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GWAS has been successfully used to identify loci associated with resistance to Aphid glycines, Spodoptera litura and Heterodera glycines in soybean, Ostrinia furnacalis in maize, Melanaphis sorghi in Sorghum, Sitodiplosis mosellana and Diuraphis noxia in wheat at the whole-genome level. [16][17][18][19][20][21][22] However, GWAS for S. avenae resistance in wheat has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The exact nature of the genetic control of RWA resistance is not yet fully understood. A recent genome wide association study (Kisten et al., 2020) validated that QTL Xgwm 1017 (on 6A) (Castro et al., 2008), Xwmc 264 (on 3A), and Xbarc 109 (on 5B) (Riccardi et al., 2010), which were reported to be associated with resistance gene DnCI2401 on chromosome 7D (Tulpová et al., 2019), were also associated with Dn4 located on chromosome 1D (Dong et al., 1997).…”
Section: Introductionmentioning
confidence: 99%